(untitled) (Heritage, 2021)
The paper analyzes the appearance of the ordinary and the everyday in the essays of Borislav Radović, which is most often manifested through the character of a small man. In the trivial and mundane, the writer finds the sublime and the important, which often receives a mythological framework. The work also deals with the writer’s position of artist-walker, flanner, which introduces a predominantly modernist line in Radović’s essays. The analysis method and the close reading method seek to give an overview of the rich gallery of little people in the essay book Some Things. The aim of the paper is to give an insight into the ways in which Borislav Radović records little and usually in everyday life, which after the artistic processing receives the outlines of the unusual and mysterious. Through various procedures (enumeration, ironicity, mythologization) and in different forms, the writer provides an opportunity for the reader to reconsider the reasons why a small man often remains out of focus of art. The results of the paper show that Radović’s essays offer a different image of the little man, not naturalistic or veristic but not idealistic, which represents an innovative approach to a marginalized topic in recent Serbian essay writing.